CATCH TRENDS OF CATFISHES TACHYSURUS THALASSINUS AND T. TENUISPINIS BASED ON EXPLORATORY DATA FOR THE PERIOD FROM 1966 TO 1976 - Krishnamurthy, B (Indian Journal of Fisheries, 2011)
The fluctuations noticed in the total catches/catch rates in respect of T.thalussinus are perhaps due to fishery independent factors. But in regard to T.tcnuispinis there are reasons to believe that they are fishery dependent.